Ethics (C. U. P, 1998)
This fourth Companion to Ancient Thought is devoted to ancient ethics. The chapters range over the ethical theories of all the major philosophers and schools from the earliest times to the work of the Hellenistic philosophers. There is a substantial introduction which considers the question of what is distinctive about ancient ethics, and an extensive bibliography. This collection provides a sophisticated and accessible introduction to the moral theories of the ancient world.